2017
DOI: 10.18632/oncotarget.20931
|View full text |Cite
|
Sign up to set email alerts
|

The association of matrix metalloproteinase-9 promoter polymorphisms with gastric cancer risk: a meta-analysis

Abstract: Conclusions: Our meta-analysis results demonstrated that MMP-9-1562C/T promoter polymorphisms increase the risk of developing gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Most data confirming the involvement of these polymorphisms in the formation of malignant tumors were obtained for the rs1799750 allele of the MMP1 gene. This polymorphism was shown to be associated with cancer of the esophagus (esophageal adenocarcinoma) [25][26][27][28] and stomach cancer [29][30][31][32]. The study of Okada et al [33] showed the association between rs17576 MMP9 and stomach cancer both independently and within the CAA rs3918242-rs17576-rs17577 MMP9 haplotype.…”
Section: Polymormentioning
confidence: 99%
See 1 more Smart Citation
“…Most data confirming the involvement of these polymorphisms in the formation of malignant tumors were obtained for the rs1799750 allele of the MMP1 gene. This polymorphism was shown to be associated with cancer of the esophagus (esophageal adenocarcinoma) [25][26][27][28] and stomach cancer [29][30][31][32]. The study of Okada et al [33] showed the association between rs17576 MMP9 and stomach cancer both independently and within the CAA rs3918242-rs17576-rs17577 MMP9 haplotype.…”
Section: Polymormentioning
confidence: 99%
“…Numerous studies showed the connection between the MMP1 and MMP9 polymorphic loci and the development of oncological diseases of the digestive system [25][26][27][28][29][30][31][32][33]. Most data confirming the involvement of these polymorphisms in the formation of malignant tumors were obtained for the rs1799750 allele of the MMP1 gene.…”
Section: Polymormentioning
confidence: 99%
“…The discussed polymorphism was analyzed not only in the context of the central nervous system diseases Certain reports indicate its association with cardiovascular diseases ( Mittal et al, 2014 ), prostate cancer ( Kiani et al, 2020 ), gastric cancer ( Peng et al, 2017 ), T-cell acute lymphoblastic leukemia ( Lin et al, 2017 ), autoimmune diseases ( Li et al, 2017 ), and chronic periodontitis ( Mashhadiabbas et al, 2019 ). For example, the allele T results in the increase in MMP-9 levels in the serum of cardiovascular patients, and it is associated with a nearly doubled risk of cardiac death and significantly lower survival rates ( Blankenberg et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of neoplasms, e.g., people with CT + TT genotype, who additionally had diabetes and smoked, were at a 3.52 times higher risk of developing prostate cancer ( Kiani et al, 2020 ). In the case of gastric cancer, the meta-analysis showed that carriers of the TT genotype were at 1.666 times higher risk of that cancer when compared to carriers of the CC genotype ( Peng et al, 2017 ). The most recent publications also report the relationship between the MMP-9-1562C/T polymorphism and the risk of pre-eclampsia or breast cancer and its aggressiveness ( Gannoun et al, 2021 ; Bartnykaitė et al, 2022 ; Huang et al, 2022 ; Yan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%